Práticas de ensino de Língua Portuguesa para surdos em escolas bilíngues: possibilidades de aprendizagem - Valle, Juliana Prudente Santana do Valle (2023)
In 2021, Law 14.191 is enacted, which considers bilingual education as an independent teaching modality. It includes Libras as the first language and written Portuguese as the second language of the deaf. Thus, there is a need to seek ways to improve the process of teaching and learning Portuguese Language (LP) for the deaf. In this case, we problematize: a) What teaching practices of written Portuguese are used by teachers of deaf students in the context of Bilingual School in the final years of elementary and high school? and b) What are the practices of reading and writing experienced by deaf students in Bilingual School that contribute to the learning of written Portuguese? Thus, we defined as a general objective to investigate the practices of teaching written LP to deaf people in a Bilingual School. The specific objectives are, to identify and describe the reading and writing practices that favor the learning of written LP for the deaf; to characterize the methodologies - the teaching and assessment strategies - of written LP for deaf students enrolled in a Bilingual School. The type of research chosen was the case study and document analysis, being a qualitative research, involving a bilingual school in the Midwest of the country, as well as LP teachers of that school. As data collection tools, we used the document analysis of the school's Political Project, the semi-structured interview conducted with the LP teachers, and the observation of both the bilingual school and the teachers' classes. The data obtained were analyzed in the light of studies pointed out by theorists such as: Thoma (2011), Neves and Fernandes (2013), Svartholm (2014), Müller and Karnopp (2015), Müller (2016), Albres (2017), Ruzza (2022) and Corrêa (2022), who outlined the concepts of structure and rationale of the bilingual school for the deaf. The results of this research reinforce the importance of bilingual school in the teaching and learning process of the deaf student, as the best prepared space for this teaching to happen, since this school will consider the specificities of deaf students in the teaching and learning process, as well as that the LP teaching practices for the deaf need to be based on visual pedagogy, since they involve visual aspects, which is the means of language acquisition of the deaf. It was also realized that it is a great challenge to have an education based on linguistic and cultural differences of deaf people in a bilingual context, and it is necessary to expand the training of teachers and their preparation to provide pedagogical practices that provide the learning of the Portuguese language in written modality for deaf students.